Integrating the export distribution channels after an acquisition - Ajanko, Maaria (My University, 2014)
This thesis is based on studying integration synergies in a merger or acquisition situation with the interest in distribution channel integration. M&As seem to be forever popular and nowadays companies often use them as a certain kind of strategy to develop their business. M&As have attracted research for decades and also distribution in M&As has been found interesting. Moreover, research often concentrates to the horizontal M&A´s potential synergies that emerge in the integration process and so is the case also in this study as the core issue is to study the integration of the distribution channels and its potential synergies. This study concentrates on a single case, an acquisition which took place in 2011. The case consists of two Finnish companies operating in the same business field. Both of the companies are very export orientated, which gives this study its export view. As the companies operate in the same field this acquisition falls into the categorization of horizontal acquisition. The objective of the thesis is to study how the export channels could be integrated after an acquisition? This research question is divided again to three sub-questions asking how the distribution channels of the acquirer and acquired company are organized, what is pursued by the post-acquisition distribution channel integration and what are the integration challenges especially from the logistics point-of-view. The framework was built from the basis of the literature used in this thesis. The framework combines M&A process and distribution channels to a one united model which presents the progress of this thesis. The study was carried out as a qualitative research and as a holistic single case study. The data used in the research includes two interviews, other material from the case companies and also material of the companies collected by the author independently from different sources. There were many motives for the acquisition as usual. From the research results one can find that the integration process is still very ongoing and the synergies have not yet been fully discovered but also they are there to be found. The concentration of the research was in the export distribution which proved to be meaningful since the exports markets of the case companies were found to be quite complementary. The research results brought up also other issues concerning the post-acquisition integration process rather than the distribution channels and export. M&As are always a risky business. The final result can never be predicted. No matter how good the merging companies look on paper the practice is not the same. The acquisition process of this case has not ended yet and there lies potential synergy benefits to be discovered if enough effort is used to go through the process right.